MAMMAL FAUNA FIRST FOUND IN ALLUVIAL-SPELEOGENIC FORMATIONS OF THE LATE NEOPLEISTOCENE AND HOLOCENE, NORTHERN URALS, LOCALITY CHEREMUKHOVO-1 - Strukova T.V.; Bachura O.P.; Borodin A.V.; Stefanovskii V.V. (My University, 2006)
Based on results of multidisciplinary study, it is shown that locality Cheremukhovo-1 is of a new taphonomic type in the Urals and characterizes interval of geological record formerly unknown for the late Neopleistocene of the region. Presented in the work are lithologic characterization of beds, dating results, and description of paleontological material (Vertebrata remains) and palynological spectra. The locality is correlated with burials known in other regions and can be regarded as one of the reference sections of upper Neopleistocene-Holocene deposits in the northern Urals. © MAIK "Nauka/Interperiodica" 2006.
Keywords: CAVE (SPELEOGENIC) AND ALLUVIAL DEPOSITS (FORMATIONS); HOLOCENE; MAMMAL FAUNA; NEVS'YANSK INTERGLACIAL; PALEOGEOGRAPHY; PALYNOLOGICAL ASSEMBLAGES; POLAR URALS GLACIAL; UPPER NEOPLEISTOCENE; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Holocene